1999
DOI: 10.1007/s11627-999-0011-3
|View full text |Cite
|
Sign up to set email alerts
|

A protocol for efficient transformation and regeneration of Carica papaya L.

Abstract: A reproducible and effective biolistic method for transforming papaya (Carica papaya L.) was developed with a transformation-regeneration system that targeted a thin layer of embryogenic tissue. The key factors in this protocol included: 1) spreading of young somatic embryo tissue that arose directly from excised immature zygotic embryos, followed by another spreading of the actively growing embryogenic tissue 3 d before biolistic transformation; 2) removal of kanamycin selection from all subsequent steps afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
7

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 25 publications
1
26
0
7
Order By: Relevance
“…In our case, however, we found kanamycin to be a very efficient selectable agent at moderately high levels for B. gracilis. This concentration of kanamycin is comparable to that utilized previously in some dicots such as papaya (Cai et al 1999) or tobacco (Holmström et al 2000). Studies with other morphogenic callus lines of B. gracilis (Aguado-Santacruz et al 2001a) have also shown the efficiency of the aminoglycoside antibiotic, paramomycin, as a selective agent, at similar concentrations to those reported in this work for kanamycin (150 mg/l).…”
Section: Discussionsupporting
confidence: 85%
“…In our case, however, we found kanamycin to be a very efficient selectable agent at moderately high levels for B. gracilis. This concentration of kanamycin is comparable to that utilized previously in some dicots such as papaya (Cai et al 1999) or tobacco (Holmström et al 2000). Studies with other morphogenic callus lines of B. gracilis (Aguado-Santacruz et al 2001a) have also shown the efficiency of the aminoglycoside antibiotic, paramomycin, as a selective agent, at similar concentrations to those reported in this work for kanamycin (150 mg/l).…”
Section: Discussionsupporting
confidence: 85%
“…Esta estratégia de controle abriu uma nova possibilidade para solução do problema da mancha anelar, de forma mais eficiente e possivelmente mais duradoura (Fitch et al, 1992;Tennant, 1996;Cai et al, 1999;Souza Jr., 1999). No entanto, quando desafiadas por isolados de outras regiões geográficas, inclusive do Brasil, as plantas da Linha 55-1 apresentaram-se susceptíveis à infecção por PRSV-P (Tennant et al, 1994).…”
Section: Estratégias De Controleunclassified
“…The PRSV resistant papaya has been commercialized, reached to end user and improved papaya is now under production in Hawaii (Tripathi et al, 2008). This study was followed by other reports mainly on improvement of PRSV tolerance in papaya via microprojectile bombardment-based transformation (Tennant et al, 1994;Cai et al, 1999;Guzman-Gonzalez et al, 2006). The deployment of transgenic papayas has showed that virus CP protein supplies durable and stable resistance to homologous strains of PRSV (Fermin et al, 2010).…”
Section: Direct Gene Transfermentioning
confidence: 71%